2005
DOI: 10.1002/clc.4960280609
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of telmisartan and ramipril on P-wave dispersion in hypertensive patients: A randomized clinical study

Abstract: Telmisartan has a much greater lowering effect on PWD and Pmaximum values than ramipril. This finding may be important in the prevention of AF in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
0
25
0
3
Order By: Relevance
“…Moreover, ARBs can inhibit Ang II activity in the left atrium, which may contribute to nonhomogeneous atrial conduction. ARBs may have a greater effect on atrial electrophysiological properties than ACEIs [29]. So ARBs has important beneficial effects on atrial stretch, interstitial fibrosis, inflammation, and eventually structural remodeling, all of which serve as a substrate for the persistence and recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ARBs can inhibit Ang II activity in the left atrium, which may contribute to nonhomogeneous atrial conduction. ARBs may have a greater effect on atrial electrophysiological properties than ACEIs [29]. So ARBs has important beneficial effects on atrial stretch, interstitial fibrosis, inflammation, and eventually structural remodeling, all of which serve as a substrate for the persistence and recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, telmisartan was shown to significantly improve the sympathovagal balance, increasing parasympathetic activity and significant reducing QT dispersion in hypertensive subjects [39]. Celik [29] suggested telmisartan has a much greater lowering effect on P-wave dispersion and P maximum values than ramipril in the prevention of AF in hypertensive patients. Sengul [40] also demonstrated the P-wave measurements and the atrial electromechanical delay (EMD) parameters in patients with newly diagnosed essential hypertension were significantly decreased after 6-month telmisartan therapy.…”
Section: Discussionmentioning
confidence: 99%
“…14,22,25,27,28,41,69,78,79,84,88,89,92 Apart from one study in which there was a greater reduction of left ventricular hypertrophy with an ARB, 89 there were no differences between ACE inhibitor and ARB groups. Only one study evaluated a DRI; it found similar effects between aliskiren and an ARB.…”
Section: Left Ventricular Mass or Functionmentioning
confidence: 98%
“…to improve two parameters shown to be independent predictors of atrial fibrillation. 70 Further, and more sophisticated information on the effects of the drug treatment on cardiac morphology, will come from the results of ongoing studies performed in the context of the already mentioned ONTARGET Trial, in which the use of magnetic resonance for assessing LV mass index will provide well defined data on the impact of the drug on hypertensionrelated cardiac organ damage. 71,72 Clinical studies carried out in human hypertension, however, have also allowed us to define the effects of the chronic Ang II blockade via telmisartan on vascular structure and function.…”
Section: Reviewmentioning
confidence: 99%